Shadows and shortfalls: Unraveling the relationship between informal economies and fiscal capacity - Wijaya, Alif Sukhairi; Wijaya, Suparna (Educoretax, 2025)
This research aims to analyze the effect of the shadow economy on tax revenue through a Systematic Literature Review (SLR) approach. The shadow economy, which encompasses unrecorded and unreported economic activities, has a significant impact on a country's fiscal capacity. The SLR method was used by conducting a systematic search of the Scopus, Web of Science, and Science Direct databases for publications from 2010-2024. From 1,235 identified articles, 42 articles were extracted and analyzed in depth based on established inclusion and exclusion criteria. The review results show that the shadow economy consistently correlates negatively with tax revenue, with varying magnitudes of influence based on country characteristics, economic structure, and taxation systems. Determinant factors that strengthen this relationship include high tax burdens, regulatory complexity, corruption, low institutional effectiveness, and the level of public tax awareness. This study also identifies several effective tax policy mechanisms in mitigating the negative effects of the shadow economy, including digitalization of tax administration, enhancing the capacity of tax authority institutions, and voluntary compliance programs. The theoretical and practical implications of these findings provide a comprehensive information foundation for policymakers in designing optimal tax revenue strategies amid informal economy challenges.